Genetic Variability of CYP2C8, CYP2C9, and CYP3A4 Across European Populations: Implications for Pharmacogenetics - Borówka, Karolina; Tymińska, Paulina; Frączek, Julia; Kawka, Natlia; Machnik, Grzegorz (Quality in Sport, 2026)
Cytochrome P450 (CYP) enzymes are membrane-bound hemoproteins responsible for the metabolism of numerous important compounds. In humans, they are responsible for nearly 80% of oxidative reactions and approximately 50% of total drug elimination, mainly within the CYP1–CYP3 families. The CYP3A4 isoenzyme, involved in the metabolism of around 50% of drugs used in clinical practice, along with the highly polymorphic CYP2C9 and CYP2C8 genes, are key members of the cytochrome P450 subfamily. Their genetic variability, which may result in abolished, quantitatively or qualitatively altered or enhanced metabolism, varies among populations and geographical regions. This review presents the frequency and diversity of CYP2C8, CYP2C9 and CYP3A4 alleles across European countries.